2012
DOI: 10.1080/08995605.2012.716265
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the OCEAN.20: A 20-Item Five-Factor Personality Measure Based on the Trait Self-Descriptive Inventory

Abstract: We report on the development of a short measure of the Big Five model of personality. In Study 1, we created three versions (15, 20, and 25 items) of the Trait Self-Descriptive Inventory (TSD), a Big Five personality measure developed by Tupes and Christal (1992). These short measures were confirmed using confirmatory factor analysis in Study 2. Studies 3 and 4 compared the predictive validity of a 75-item TSD against that of the shortened scales. Results suggest that a 20-item version (the OCEAN.20) is a usef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The revised five-factor model of personality component (FF-B) that consists of 13 items for the theoretically defined five factors has good model fit. Previous studies have reported similar findings on the five-factor personality traits (34)(35)(36). In addition, this finding provides further evidence to support the finding of a previous study that was done by Yusoff (37) on the psychometric properties of USMaP-i in the medical student population.…”
Section: Discussionsupporting
confidence: 89%
“…The revised five-factor model of personality component (FF-B) that consists of 13 items for the theoretically defined five factors has good model fit. Previous studies have reported similar findings on the five-factor personality traits (34)(35)(36). In addition, this finding provides further evidence to support the finding of a previous study that was done by Yusoff (37) on the psychometric properties of USMaP-i in the medical student population.…”
Section: Discussionsupporting
confidence: 89%
“…These approaches identify personality traits that in- or decrease the likelihood of disinhibited online communication. One of the two personality models that are predominantly used in this context is the Big 5 model of personality, which spans the five personality factors of openness, conscientiousness, extraversion, agreeableness, and neuroticism (O'Keefe et al, 2012 ). For example, Kokkinos et al ( 2013 ) found that high extraversion and conscientiousness lower the likelihood that an individual engages in cyberbullying.…”
Section: Introductionmentioning
confidence: 99%
“…Participants were excluded if they were currently taking any medication. Participants completed the OCEAN.20 personality inventory 49 and the Situational Vertigo Questionnaire (SVQ) questionnaire 50 . The OCEAN.20 inventory includes twenty items, five of which are each dedicated to each of the Big Five personality traits 51 , e.g., Openness, Conscientiousness, Extraversion, Agreeableness, Neuroticism.…”
Section: Methodsmentioning
confidence: 99%
“…Facial electromyography (fEMG) was recorded at 1000 Hz from the corrugator supercilii and zygomaticus major via the Bionomadix ambulatory psychophysiology system (BIOPAC). fEMG data were processed as follows: (1) bandpass filter applied at 49-51 Hz to remove 50 Hz noise, (2) filtered between 20 and 400 Hz, (3) rectified and smoothed via linear envelope (9 Hz filter), and (4) subjected to root mean square transformation 49 , 50 . Skin Conductance Level (SCL) was also recorded at 1000 Hz via the Bionomadix system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation